The Inside of the Cup $1 (BVolume 03s - Churchill, Winston, 1871-1947 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Inside of the Cup $1 (BVolume 03" by Winston Churchill is a novel published in 1913. When John Hodder becomes rector of an elite church serving the wealthy in a Midwestern city, he's expected to preach a comfortable Christianity that doesn't challenge corporate power or concentrated wealth. But witnessing poverty and corruption sparks a spiritual crisis that transforms his ministry. His decision to preach Jesus's core message of loving and serving mankind ignites a fierce battle between the old guard and those moved by his transformation. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Inside_of_the_Cup
Release date is 2004-10-17
Produced by David Widger
Keywords: Christian life -- Fiction; Attitude change -- Fiction; Christian ethics -- Fiction; Conscience -- Religious aspects -- Fiction